Designing the Concept and Design Elements of MSME X Room Deodorizer Packaging Using Kansei Engineering and Fuzzy Logic Methods - Purnama Sari, Novi; Emaregita Indah Patricia; Siringoringo, Gabriel Angelica Margaretha; Ganjaryadi Yaskur Ramadhan (International Journal of Industrial Engineering and Engineering Management, 2025)
Air fresheners are comfort-supporting products widely used for room freshness. The packaging used by MSME X for air freshener products is only plain plastic without product identity, and it still has shortcomings in terms of functionality such as product protection, ease of use, and ease of obtaining product information. The purpose of this research is to develop concepts and design elements for MSME X air freshener packaging by considering consumer needs. This study analyzed the design of MSME X air freshener packaging using the Kansei Engineering method to translate consumer perceptions of packaging design. The data obtained was processed using Principal Components Analysis (PCA) to analyze the Kansei words collected by questionnaire to derive design concepts. The Quantification Theory Type 1 (QTT-1) method was also used to measure the relationship between design elements and design concepts. An evaluation was then conducted using the fuzzy logic method to determine whether the design elements used aligned with the selected concepts. The PCA method in this study resulted in 1 selected Principal Component (PC) which was implemented as a concept, namely "Common and Efficient". Determination of design elements using the QTT1 method resulted in selected elements, namely X1.5 (ivory), X2.9 (oval), X3.9 (hanger + window), X4.1 (medium), X5.6 (sliding tray), X7.4 (directly printed on the packaging) for the Efficient concept and X1.2 (rigid plastic), X2.4 (standing pouch), X3.8 (air hole + hanger), X4.2 (small), X5.7 (flip top), X6.4 (fresh + matching aroma) and X7.5 (no design) for the Common concept.